Da Vinci’s friction for granular media - Assaf Miron; Rafael Tadmor; Victor Multanen; Shmulik Pinkert (Scientific Reports)
Abstract The concept of friction was integrated into the broader field of tribology in the 20th century. Here, we revive the older friction coefficient concept and show that it is the defining parameter for a family of granular materials. We show, for the first time, that kinetic friction coefficients of such systems can be described as a function of the lubricating fluid and the shape of the granules, without any fitting parameters. With this, we define the value and conditions for the minimal friction of this system and show how it can increase depending on the properties of the system. This paper shows that the minimum possible friction for an assembly of granular media is the same universal constant of ¼ that da Vinci identified for kinetic friction between two rigid bodies.